Psychosocial and Clinical Determination of Quality of Life of Breast Cancer Patients at dr. Adnaan WD Payakumbuh Regional Hospital in 2026 - Iwan Gusmana, Azzahra; Gusta Anggraini Nursal, Dien; Widoyo, Ratno (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Breast cancer is a leading cause of female mortality in Indonesia. The majority of women with breast cancer face physical and psychological pressures such as the fear of death, changes in body image, and fatigue during treatment, which seriously impact their psychological health and quality of life. Globally, the prevalence of depression among women with breast cancer is estimated to be around 30.2%, and breast cancer patients have a higher incidence of depression compared to patients with other malignant tumors. This study aims to determine the association between depression and quality of life (QoL) in 40 patients at RSUD dr. Adnaan WD Payakumbuh. This cross-sectional study employed non-probability sampling and structured interviews. We performed univariate, bivariate (chi-square), and multivariate (logistic regression) analysis. Results indicate significant associations between QoL and depression (p<0.001), age (p=0.003), occupation (p=0.028), stage (p=0.019), and treatment duration (p=0.037). Conversely, education (p=0.811) and treatment type (p=0.970) show no significant relationship. Duration and age emerged as dominant predictors in the relationship between depression and QoL of breast cancer patients at RSUD dr. Adnaan WD Payakumbuh in 2026. We recommend routine depression screenings for early psychological intervention. In addition, continuous health education regarding the disease, treatment, and ways to manage therapy side effects is necessary so that patients are better prepared for long-term treatment.